198 Replacing cottonseed meal and sorghum grain with corn dried distillers grains with solubles in lamb feedlot diets: Growth performance and ruminal fluid parameters. (29th July 2019) - Hodges, Kade; Whitney, Travis R; Ramsey, Shawn
Abstract: Effects of replacing cottonseed meal (CSM) and sorghum grain with dried distillers grains with solubles (DDGS) in Dorper ram lamb (n = 46) feedlot diets on growth performance and rumen fluid parameter were evaluated. In a randomized design study, lambs were individually fed ad libitum 70.9% concentrate diets for 56 d in individual pens. The positive control diet (CNTL) contained CSM, sorghum grain, and other concentrates, but no DDGS. Four treatment diets were similar to CNTL, but had no CSM which was replaced 0% (0DDGS), 33% (33DDGS), 66% (66DDGS) or 100% (100DDGS) of the sorghum grain. Lambs fed CNTL were compared to 0DDGS and linear and quadratic effects were evaluated within the four DDGS diets. A treatment × day interaction was observed (P < 0.001) for lamb BW, but not for ADG, DMI, or G:F (P > 0.10). Lambs fed CNTL had greater (P ≤ 0.02) BW on d 42 and 56 and greater (P < 0.01) overall ADG and G:F than lambs fed 0DDGS. On d 42 and 56, lamb BW quadratically increased (P ≤ 0.04) as DDGS increased in the diet. Averaged across all days, ADG quadratically increased (P < 0.001) and DMI and GF tended to quadratically increase (P ≤ 0.08) as DDGS increased in the diet. On d 56, ruminal pH quadratically decreased (P < 0.001), acetate linearly increased (P < 0.001) and acetate:propionate tended to linearly increase (P = 0.08) as DDGS increased in the diet. Results indicated that lamb growth performance is enhanced when CSM is used to increase dietary CP (CNTL vs. 0DDGS) and that all of the CSM and up to 66% of the sorghum grain can be replaced by DDGS (66DDGS) without negatively affecting growth performance.